Fighting the sprawl: restructuring the seam between the rural and urban landscapes through consolidation, integration and intensifcation in Cape Town - Louw, Pieter (School of Architecture, Planning and Geomatics, 2025)
The central theme of this research project is the relationship between humanity and the environment. Specifcally where this relationship is at its biggest confict, where settlements and open space meet, on the peripheries of cities. Traditionally, the settlement form of the Cape maintained a dynamic balance between the landscapes of society, wilderness, rural and urban. This balance was disrupted through Modernism and Apartheid planning which lead to segregated, fragmented and low-density urban landscapes. Through outdated planning policies, engineering standards and speculative development models, this balance is still increasingly disrupted, manifested in the form of lateral sprawl. The urban landscape, which is considered by the status-quo as the dynamic landscape, places growing pressure on the rural and wilderness landscapes. The need to restrict the lateral growth of cities is globally recognised and one unsuccessful tool utilised in the Greater Cape Town Metro to prevent urban sprawl, is the urban edge policy. This research project argues that a line that exists only on paper, such as an urban edge policy which promotes compaction, is not a suffcient mechanism to address urban sprawl. Compaction is only one aspect of mitigating sprawl. It argues that the edge is a landscape, not a line and explores the notion that a spatial proposition is necessary that consolidates and integrates the rural and urban interface zone and restructures the peripheral urban landscape. That this landscape could, through consolidation, integration and intensifcation, target and mitigate the drivers of sprawl